Ethnicity and Nonsurgical Rhinoplasty. (2nd May 2022) - Ziade, Georges; Mojallal, Ali; Ho-Asjoe, Mark; Arenas, Juan Carlos; Ascher, Benjamin
Abstract: Background: Nonsurgical rhinoplasty is a procedure that is gaining popularity in aesthetic clinics particularly because of its minimally invasive nature compared with surgery. It is recognized that there are ethnic variations in nose injection techniques and planned aesthetic outcomes. Objectives: The objective of this study was to explore experts' views about the ethnic differences in the anatomical features of the nose and procedure-related considerations in nonsurgical rhinoplasty. Methods: Using a priori set topics and questions, 4 expert aesthetic physicians, from 4 different ethnic backgrounds and working in 4 different regions, were asked to describe the essential elements to be considered when planning a nonsurgical rhinoplasty, including product choice, injection technique, safety measures, and any practical hints to facilitate achieving the desired outcome. Results: All invited experts responded to the full set of questions. There were similarities between the treating physicians in some of the technical steps. Nevertheless, there were several differences identified regarding baseline anatomy and patient expectations that could be attributed to ethnicity. Patients' and physicians' expectations regarding a successful nonsurgical rhinoplasty can vary depending on their ethnic backgrounds. Therefore, with the current global ethnic and cultural diversities, in addition to the knowledge of the nasal anatomy and safe injection techniques, it is imperative that aesthetic practitioners have full awareness and a good understanding of these ethnic variations. Conclusions: Nonsurgical rhinoplasty is a highly demanded aesthetic procedure. Patients' ethnic differences need to be carefully taken into consideration when discussing, planning, and performing nasal fillers injection.